Antecedents of Job Satisfaction and the Influence on Turnover Intention - Srimindarti, Ceacilia; Oktaviani, Rachmawati Meita; Hardiningsih, Pancawati (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2017)
This study aimed to examine the effect of the antecedent of job satisfaction on job satisfaction, the influence of leadership style, organizational commitment and job satisfaction on turnover intention and whether job satisfaction was able to mediate the relation of antecedent of job satisfaction on turnover intention. The respondents in this study were employees at consulting firms in Semarang. The analysis instrument in this research was the multiple regression. The study showed that leadership style and organizational commitment had positive influence on job satisfaction. The other result of this study showed that leadership style, organizational commitment and job satisfaction had negative influence on turnover intention. With the proven fact of the influence of leadership style, organizational commitment and job satisfaction on turnover intention, the managers of consulting firms, therefore, should use leadership style that fit with employees, should try to increase the organization’s commitment to employees so they knew that they were a part of the organization and to maintain their membership in the organization and should improve employee satisfaction in order to reduce the turnover intention among employees.